2020
DOI: 10.1590/0004-282x20200025
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging investigation of memory changes in migraine: a systematic review

Abstract: ABSTRACT Background: Individuals with migraine usually complain about lower memory performance. Diagnostic methods such as neuroimaging may help in the understanding of possible morphologic and functional changes related to the memory of those individuals. Therefore, the aim of this review is to analyze the available literature on neuroimaging changes related to memory processing in migraine. Methods: We searched the following databases: Pubmed/Medline, Psycinfo, Science Direct, Cochrane and Web of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The severity of migraine symptoms has been found to be positively correlated with the strength of connections in the hypothalamus and inversely correlated with connections in the prefrontal cortex (Coppola et al, 2020). These structural and functional irregularities within pathological brain regions and networks associated with migraine are linked to overall dysregulation in the integration and processing of pain components during migraine attacks (David et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The severity of migraine symptoms has been found to be positively correlated with the strength of connections in the hypothalamus and inversely correlated with connections in the prefrontal cortex (Coppola et al, 2020). These structural and functional irregularities within pathological brain regions and networks associated with migraine are linked to overall dysregulation in the integration and processing of pain components during migraine attacks (David et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric disorders Depression, anxiety, panic disorder, bipolar disorder, personality disorders, stress, suicide attempts [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Sleep disorders Insomnia, parasomnias, restless leg syndrome, sleep apnea, poor sleep quality and duration [30][31][32][33][34][35] Chronic pain Fibromyalgia [36][37][38][39][40] Epilepsy Seizures, independent of type [41][42][43][44] Cognitive dysfunction Memory changes [45][46][47] Limbic system in migraine allow for the management of patients to be individualized and adjusted accordingly. Such approaches would be valuable in improving the treatment of migraine and its related problems.…”
Section: Specific Conditions Referencesmentioning
confidence: 99%
“…A review by David et al. (2020) found that neuroimaging revealed increased activation and abnormal functioning of cortical areas intrinsic to memory processing and formation, the integration of sensory information and temporal cortical areas responsible for language and visuospatial functioning (see also Ravishankar & Demakis, 2007). Similarly, another review found abnormal functional connectivity in various networks including salience, sensorimotor, executive, attention, limbic and default mode networks and networks related to visual processing (Chong et al., 2019).…”
Section: Introductionmentioning
confidence: 99%